1996
DOI: 10.1007/bf00127046
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and adsorptive separations: A review and bibliographical update (1994)

Abstract: This paper provides a review of the 1994 journal literature and complete bibliography concerned with adsorptive separations. The references are taken from the 45 most important chemical engineering journals. This paper provides an update to the literature as provided in previous bibliographic papers 1995). References for membranes and membrane-type separations (for 1992-1993) were the subject of a separate bibliographic paper (Ray 1994), due to the number of papers now published on this topic each year. A rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Many studies have shown that the boundary-layer diffusion is the rate controlling step in systems characterized by dilute concentrations of adsorbate, poor mixing, and small particle size of adsorbent. Whereas the intraparticle diffusion controls the rate of adsorption in systems characterized by high concentrations of adsorbate, good mixing, and big particle size of adsorbent [26,27]. Also, it has been noticed in many systems that boundary-layer diffusion (external mass transfer) is dominant at the beginning of adsorption during the initial adsorbate uptake, then gradually the adsorption rate becomes controlled by intraparticle diffusion after the adsorbent's external surface is loaded with the adsorbate [25][26][27].…”
Section: Sorption Mechanismmentioning
confidence: 98%
“…Many studies have shown that the boundary-layer diffusion is the rate controlling step in systems characterized by dilute concentrations of adsorbate, poor mixing, and small particle size of adsorbent. Whereas the intraparticle diffusion controls the rate of adsorption in systems characterized by high concentrations of adsorbate, good mixing, and big particle size of adsorbent [26,27]. Also, it has been noticed in many systems that boundary-layer diffusion (external mass transfer) is dominant at the beginning of adsorption during the initial adsorbate uptake, then gradually the adsorption rate becomes controlled by intraparticle diffusion after the adsorbent's external surface is loaded with the adsorbate [25][26][27].…”
Section: Sorption Mechanismmentioning
confidence: 98%
“…Many studies have shown that the boundary layer diffusion is the rate controlling step in systems characterized by dilute concentrations of adsorbate, poor mixing, and small particle size of adsorbent [2,3]. Whereas the intraparticle-diffusion controls the rate of adsorption in systems characterized by high concentrations of adsorbate, vigorous mixing, and large particle size of adsorbent.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas the intraparticle-diffusion controls the rate of adsorption in systems characterized by high concentrations of adsorbate, vigorous mixing, and large particle size of adsorbent. Also, it has been noticed in many systems that film diffusion (external mass transfer) is dominant at the beginning of adsorption during the initial adsorbate uptake, and then the adsorption rate becomes controlled by intraparticle-diffusion after the adsorbent's external surface becomes loaded with the adsorbate [1,2].…”
Section: Introductionmentioning
confidence: 99%